EFEKTIVITAS PENAMBAHAN NIKEL PADA PENCAIRAN BATUBARA PERINGKAT RENDAH MENGGUNAKAN KATALIS ALAMI LIMONIT - Yusnitati Yusnitati (Jurnal Energi dan Lingkungan (Enerlink), 2006)
Coal liquefaction of brown coal from South Banko coal was conducted using 5 Lautoclave batch reactor. the effect of nickel addition on the activity of naturallimonite catalyst from Soroako was investigated by comparing the amount ofnickel addition to the reaction.Tthis study showed that original nickel ferritepresent in natural limonite did not play a significant role in increasing the activityof iron compounds in limonite. This study was also pointed out that ironcompound (Î±-FeOOH) was the major compound for obtaining high oil yield inliquefaction of low rank coal.Kata kunci: liquefaction, low rank coal, nickel ferrite, soroako limonite